2023
DOI: 10.3390/jpm13050768
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in Young Adults in Spain: Epidemiology and Risk Factors by Age

Abstract: Introduction: Recent research has highlighted an increased incidence of ischemic stroke (IS) in young adults, along with a higher percentage of vascular risk factors at younger ages. This study aimed to estimate the in-hospital incidence of IS and associated comorbidities by sex and age group in Spain. Methods: A retrospective analysis of the Spain Nationwide Inpatient Sample database from 2016 to 2019 was conducted, which included adult patients with IS. In-hospital incidence and mortality rates were estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…In a Ludhiana population-based study, DLP was observed in 15% of young strokes [ 5 ]. Various studies from European countries reported DLP rates ranging from 26.4% to 52.7% [ 10 , 11 , 14 ]. Our study reports a lower frequency of smoking as compared to the data from the Western world [ 11 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a Ludhiana population-based study, DLP was observed in 15% of young strokes [ 5 ]. Various studies from European countries reported DLP rates ranging from 26.4% to 52.7% [ 10 , 11 , 14 ]. Our study reports a lower frequency of smoking as compared to the data from the Western world [ 11 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Real-time TEE in patients with normal TEE can help in reclassifying patients in the undermined category by increasing the yield of the pick rate of the left ventricle (LV), left atrial (LA) clots, and PFO. Western literature reports PFO and atrial septal aneurysm (ASA) as the most common aetiologies behind cardioembolic strokes [ 14 , 20 ].…”
Section: Discussionmentioning
confidence: 99%